Analysing the national and institutional policy landscape for foreign academics in Thailand: opportunity, ambivalence and threat. Issue 4 (4th July 2019) - Burford, James; Uerpairojkit, Thornchanok; Eppolite, Mary; Vachananda, Tittaphan
ABSTRACT: While academic expatriation is a longstanding global phenomenon, Thailand has emerged in recent years as an increasingly popular destination for internationally mobile academics. The objective of this article is to identify current policy dispositions towards foreign academics at the national and institutional levels in Thailand. The article finds that within Thai higher education policy discourse, foreign academics are framed in three primary ways: as opportunities, as absent or unimportant, and as threats to Thailand. While foreign academics are often cast as experts who might accelerate the economic development of the nation and enhance the competitiveness of the Thai higher education sector, they may also be presented as threats to Thai culture, values and security. However, the most prevalent disposition found in this study was one of absence and marginality, suggesting a high degree of ambivalence toward foreign academics. The article concludes with implications for future researchers and policymakers to consider.